2010
DOI: 10.1186/1546-0096-8-19
|View full text |Cite
|
Sign up to set email alerts
|

Bullous lesions as a manifestation of systemic lupus erythematosus in two Mexican teenagers

Abstract: Rarely, systemic lupus erythematosus (SLE) presents with bullous lesions due to severe edema and hydropic degeneration of the basal layer, or as a subepidermal blistering disease. Here, we describe two Mexican teenagers, one with SLE with blisters and another with bullous SLE. We also discuss the mechanisms and clinical implications of lesion formation in patients with SLE and bullae.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 19 publications
1
27
0
1
Order By: Relevance
“…An association between BSLE and lupus nephritis is debated . In our literature review of pediatric BSLE cases, we found 21 of 33 (64%) cases that had renal involvement, and 12 of these (36%) were confirmed lupus nephritis.…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations
“…An association between BSLE and lupus nephritis is debated . In our literature review of pediatric BSLE cases, we found 21 of 33 (64%) cases that had renal involvement, and 12 of these (36%) were confirmed lupus nephritis.…”
Section: Discussionmentioning
confidence: 76%
“…The pathologic mechanism underlying BSLE is thought to be driven by autoantibodies targeting the NC1 domain of collagen VII, which is a component of the anchoring fibrils of the dermoepidermal junction; its immune‐mediated destruction may result in separation of the skin layers and formation of bullae. It has been hypothesized that the pathogenesis of BSLE begins with deposition of collagen VII in an ectopic location, such as the kidney, and subsequent production of autoantibodies to this abnormally located protein . Another hypothesis involves an initial interface dermatitis secondary to SLE exposing autoreactive T‐cells to previously sequestered antigens, including collagen VII .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1,7 Nevertheless, primarily blistering diseases have been anecdotally reported to occur in patients with both cutaneous and SLE. The presence of bullae in conjunction with systemic manifestations and specific autoantibodies should serve as an alert for BSLE diagnosis.…”
Section: Discussionmentioning
confidence: 99%